A Moderated Mediation Model of Emotional Labor and Service Performance: Examining the Role of Work–Family Interface and Physically Active Leisure. Issue 1 (1st January 2020) - Wu, Cindy; Chen, Yen-Chun; Umstattd Meyer, M. Renée
ABSTRACT: Taking a resource perspective of work–family interface, we tested a moderated mediation model where physically active leisure moderates the influences of emotional labor strategies (surface vs. deep acting) on employee in-role (i.e., job performance) and extra-role service performance (i.e., extra-service behavior and cooperation behavior) through work–family interface (work-family conflict and work-family enrichment). Conditional indirect and direct effects were tested by PROCESS with a matched sample of 374 hair designers and their supervisors. The results show that work-family conflict mediates the negative relationships between surface acting and employee service performance, while work-family enrichment mediates the influence of deep acting on service performance. Furthermore, physically active leisure serves as a key resource that enhances the indirect effects of deep acting through work-family enrichment. We discuss the theoretical and practical implications of these findings.